Economic development and greenhouse gas emissions in the European Union countries - Lapinskienė, Giedrė; Peleckis, Kęstutis; Radavičius, Marijus (Journal of Business Economics and Management, 2015)
The paper analyses the environmental Kuznets curve (EKC) relationship between greenhouse gases and main aspects of economic development based on the panel data of 20 countries of the EU, including the data of three Baltic States, in the period 1995–2011. The fixed effect panel model was used as a framework for the analysis. The commonly used models confirmed the presence of the inverse U-shaped relationship. The novel contribution of this paper is that the factor referring to the global financial crisis was tested in expanded EKC model. Higher energy taxes, primary production of nuclear heat and R&D decrease the level of greenhouse gas emissions (GHG). The size of agriculture, industry and construction, as well as the primary production of solid fuels have a positive sign, which means that a higher value of these indicators is associated with a higher level of GHG. This implies that the analysed set of factors can be applied to adjust the EKC trend in the region and might be useful for the climate change policy adjustment.